The Ethylene Precursor ACC Affects Early Vegetative Development Independently of Ethylene Signaling - Vanderstraeten, Lisa; Depaepe, Thomas; Bertrand, Sophie; Van Der Straeten, Dominique (Frontiers in Plant Science, 2019)
The plant hormone ethylene plays a pivotal role in virtually every aspect of plant development, including vegetative growth, fruit ripening, senescence and abscission. Moreover, it acts as a primary defense signal during plant stress. Being a volatile, its immediate biosynthetic precursor, 1-aminocyclopropane-1-carboxylic acid, ACC, is generally employed as a tool to provoke ethylene responses. However, several reports propose a role for ACC in parallel or independently of ethylene signaling. In this study, pharmacological experiments with ethylene biosynthesis and signaling inhibitors, 2-aminoisobutyric acid and 1-methylcyclopropene, as well as mutant analyses demonstrate ACC-specific but ethylene-independent growth responses in both dark- and light-grown Arabidopsis seedlings. Detection of ethylene emanation in ethylene-deficient seedlings by means of laser-based photoacoustic spectroscopy further supports a signaling role for ACC. In view of these results, future studies employing ACC as a proxy for ethylene should consider ethylene-independent effects as well. The use of multiple knockout lines of ethylene biosynthesis genes will aid in the elucidation of the physiological roles of ACC as a signaling molecule in addition to its function as an ethylene precursor.